Pemberdayaan Perempuan dalam Pemanfaatan Limbah Bekas Tali Kapal - Muthia Andriani; Ardiyansyah Ardiyansyah (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: This study aims to determine the process of empowering women in the ship rope waste treatment program as an effort to improve family welfare. Research Methodology: The method used in this research is descriptive qualitative, the informants are determined based on purposive sampling technique. A total of 8 informants were selected from diverse backgrounds representing each stakeholder who played a role in program implementation. In-depth interviews were conducted to determine the community's response to program development. The implementation of this women's empowerment program is reviewed through members' internal and external factors. Results: The resulting achievements are not only able to improve the family's economy but are also able to provide space for expression for women to increase their potential. The ability to absorb knowledge related to work processes has an impact on the development of innovation in the Balanipa Group. Limitations: The limitation of research specifically only discusses the role of women without involving gender equality with the role of men in program implementation. Contribution: This research can be used as a reference for innovation and development of empowerment programs in other areas through the concept of innovation adaptation.